Thermally Stimulated Processes in the Ferroelectric Ceramic System Pb0.88Sm0.08TiO3 - García-Wong, A. C.; González-Abreu, Y.; Peláiz-Barranco, A.; Gagou, Y.; Saint-Grégoire, P. (Revista Cubana de Física; Vol 28 No 1 (2011), 2011)
This paper presents the analysis of the thermally activated processes of Pb 0.88 Sm 0.08 TiO 3 ferroelectric ceramics. The study has been carried out from room temperature to the ferroelectricparaelectric phase transition temperature. The results corresponding to the pyroelectric current and the conduction mechanisms related to the oxygen vacancies are analyzed.